PERENCANAAN PERLINDUNGAN PANTAI SAYUNG DEMAK - Ihwan Nul Hakim; M Fiqigozari; Sumbogo Pranoto; Priyo Nugroho Parmantoro (Jurnal Karya Teknik Sipil, 2014)
Sayung shore in Demak is one of many shores that its coastline has been receded quite alarming. Bedono village have the worst damage, now just five of seven hamlets exist in Bedono. Senik and Tambaksari are two retreat hamlets due to erosion. Moreover, the access roads among those hamlets were disconnected, and the sea water had flooded the settlement residence. From the years of 2000-2005, 325 Ha fish ponds were lost due to the erosion, and 110 Ha were flooded by the tide.The objective of this study is to plan Sayung shore protection. Location of the study is on western side of Sayung river with the length of coastline around 3.9 kms.The aspects of analysis are tidal currents, wave generated by wind, coastal morphology, and geological engineering. There are four alternatives of shore protections which are breakwater, revetment, groin and combinations.Combination of revetment and breakwater were analysed against coastal morphology, function, low cost structure, and workability. Revetment along the 2.3 kms will be built on the western side, and on the eastern side three units of breakwater, which each breakwater length is 100 m with 40 m breakwater gap.